The Ashley Treatment: Improving Quality of Life or Infringing Dignity and Rights? - Harnacke, Caroline (Bioethics, 2016)
The ‘Ashley treatment’ (growth attenuation, removal of the womb and breasts buds of a severely disabled child) has raised much ethical controversy. This article starts from the observation that this debate suffers from a lack of careful philosophical analysis which is essential for an ethical assessment. I focus on two central arguments in the debate, namely an argument defending the treatment based on quality of life and an argument against the treatment based on dignity and rights. My analysis raises doubts as to whether these arguments, as they stand in the debate, are philosophically robust. I reconstruct what form good arguments for and against the treatment should take and which assumptions are needed to defend the according positions. Concerning quality of life (Section 2), I argue that to make a discussion about quality of life possible, it needs to be clear which particular conception of the good life is employed. This has not been sufficiently clear in the debate. I fill this lacuna. Regarding rights and dignity (section 3), I show that there is a remarkable absence of references to general philosophical theories of rights and dignity in the debate about the Ashley treatment. Consequently, this argument against the treatment is not sufficiently developed. I clarify how such an argument should proceed. Such a detailed analysis of arguments is necessary to clear up some confusions and ambiguities in the debate and to shed light on the dilemma that caretakers of severely disabled children face.